Socioeconomic effects of collectivist and individualist education: A comparison between North and South Vietnam - Hanna Adam (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2020)
This working paper analyses the socioeconomic effects of education in two different political systems by investigating whether individuals educated in a collectivist education system are less likely to become entrepreneurs than individuals educated in an individualist system. It exploits the separation of Vietnam into a communist northern and a capitalist southern part between 1954 and 1975 to identify education in the respective systems, keeping factors such as national culture or historical background fixed. A Probit regression using survey data on 1,164 individuals suggests that being educated in the North makes it 8.6 percent less likely to become an entrepreneur than being educated in the South. This demonstrates that education in different systems may have an effect on entrepreneurial activity, although challenges such as necessitydriven entrepreneurship remain unresolved.
Keywords: L26; N35; O12; P30; R2; 330; Entrepreneurship; Education; Vietnam; Survey data; Probit regression